Method of installation septic tank / Wan Muhammad Faiq Wan Ahmad - Wan Ahmad, Wan Muhammad Faiq (Universiti Teknologi MARA, Perak, 2010)
This report is a brief discussion about the an installation method of septic tank of the type polysept ps3, which is made of fiber reinforced plastic. This practical report is produced based on the experience that has passed by me for 6 months practical training at the build site housing 114 units of terrace houses, at Kuala Berang, Terengganu Darul Iman. This report is divided into several sections and begin with the background of the company and project. I have to undergo practical training at company Nafas Permata Sdn. Bhd. which is a subsidiary company to Gemilang Mega Sdn Bhd. The main purposed of this study is to understand the real work happens at a construction site where the topics I choose are related to installation work from beginning phase of installation septic tank ready to install. After several months of my practical training at a construction site, I find the most appropriate title in the title of the report made. In this report there are also explained briefly about the types of septic tanks commonly used type of fiber reinforced polymer (FRP), concrete, and plastic material. during installation work is carried out a number of septic tank problems associated with the installation of septic tanks have been identified and this report has ended with several recommendations to resolve the perceived problems identified. In conclusion, this report can be expected to explain in more detail to their readers on how to install a septic tank from the start of work until it complete all.